The oncological safety of hysteroscopy in the diagnosis of early-stage endometrial cancer: An Israel gynecologic oncology group study. (December 2019) - Namazov, Ahmet; Gemer, Ofer; Helpman, Limor; Hag-Yahia, Nasreen; Eitan, Ram; Raban, Oded; Vaknin, Zvi; Leytes, Sophia; Lavie, Ofer; Amit, Amnon; Levy, Tally; Volodarsky, Michael; et al.
Abstract: Objective: To compare survival measures of women with early-stage endometrial cancer who underwent either hysteroscopy or a non-hysteroscopic procedure as a diagnostic procedure. Study design: An Israel Gynecologic Oncology Group multicenter study of 1324 patients with stage I endometrial cancer who underwent surgery between 2002 and 2014. Patients were divided into two groups: hysteroscopy and non-hysteroscopy (curettage or office endometrial biopsy). Clinical, pathological, and survival measures were compared between the groups. Results: There were 355 patients in the hysteroscopy group and 969 patients in the non-hysteroscopy group. The median follow-up was 52 months (range 12–120 months). There were no differences between the groups in the 5-year recurrence-free survival (90.2% vs. 88.2%; p = 0.53), disease-specific survival (93.4% vs. 91.7%; p = 0.5), and overall survival (86.2% vs. 80.6%; p = 0.22). Conclusion: Our findings affirm that hysteroscopy does not compromise the survival of patients with early-stage endometrial cancer.